2019
DOI: 10.1590/s1677-5538.ibju.2019.0132
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin monotherapy for the treatment of hypogonadal symptoms in men with total testosterone > 300 ng/dL

Abstract: Purpose The 2018 American Urological Association guidelines on the Evaluation and Management of Testosterone Deficiency recommended that 300 ng/dL be used as the threshold for prescribing testosterone replacement therapy (TRT). However, it is not uncommon for men to present with signs and symptoms of testosterone deficiency, despite having testosterone levels greater than 300 ng/dL. There exists scant literature regarding the use of hCG monotherapy for the treatment of hypogonadism in men not interested in fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Since testosterone replacement therapy for low testosterone has the potential to inhibit spermatogenesis 21 , studies have described the use of off-label drugs for the treatment of these men. 13,14,[22][23][24][25] Based on the hypothesis that spermatogenesis disruption is caused by low levels of intratesticular testosterone, 5,16,26 we analyzed the outcomes of men treated with off-label medications that knowingly increase ITT, comparing baseline and follow-up semen parameter [s] to serum levels of 17-OHP (ITT serum biomarker) and T. We discovered that men with low 17-OHP are better responders to medical treatment and, therefore, they are likely the best candidates for medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since testosterone replacement therapy for low testosterone has the potential to inhibit spermatogenesis 21 , studies have described the use of off-label drugs for the treatment of these men. 13,14,[22][23][24][25] Based on the hypothesis that spermatogenesis disruption is caused by low levels of intratesticular testosterone, 5,16,26 we analyzed the outcomes of men treated with off-label medications that knowingly increase ITT, comparing baseline and follow-up semen parameter [s] to serum levels of 17-OHP (ITT serum biomarker) and T. We discovered that men with low 17-OHP are better responders to medical treatment and, therefore, they are likely the best candidates for medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For hCG therapy, regimens have been utilized such as dosing regimens including 2000 IU human chorionic gonadotropin (hCG) weekly, with patients receiving alternating biweekly and triweekly injections. 14 Like FSH and LH, cost varies substantially, with 1 study reporting a monthly cost of$359 while pharmacies within our study reported monthly costs of less than$75 USD per month. 15 …”
Section: Introductionmentioning
confidence: 69%
“…Delivery and specific drug formulations become more complicated in FSH, LH, and hCG therapy. 10 , 14 With the exception of 1 recombinant FSH (rFSH) formulation, FSH and LH are given as injections, frequently every other day, which may be challenging for some patients to administer and are less favorable as delivery mechanisms than oral medications. 10 In FSH and LH therapy, there are basic distinctions between urinary-derived, highly purified (HP) FSH/HP LH, and rFSH and LH exists.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hCG has historically been recommended for men with TD interested in maintaining fertility or recovering sperm production in men previously on exogenous testosterone [ 5 , 10 , 11 ]. Several studies support hCG therapy to recover spermatogenesis after testosterone use but do not report the effect of hCG on symptoms or side effects [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The American Urological Association (AUA) recommends using hCG for men with TD and fertility concerns, as it can maintain sperm production, while exogenous testosterone can act as a contraceptive. There is limited research on the efficacy and safety of hCG monotherapy, particularly in men who fail to meet the biochemical criteria for conventional TRT [ 5 ]. As a result, we sought to evaluate the response of patients to hCG monotherapy.…”
Section: Introductionmentioning
confidence: 99%